Book Review: Kaushik Basu, An Economist in the Real World: The Art of Policy Making in India. Issue 3 (September 2018) - Kaushal, Leena Ajit
Kaushik Basu, An Economist in the Real World: The Art of Policy Making in India, 2015, MIT Press, USA, 1–240 pp., ₹2, 586.62 (Hardbound). ISBN: 9780262029629.